The Effect of Taxpayer Convenience, Taxpayer Compliance, and Understanding of Tax Regulations on The Use of M-Tax Application System Services - Balqis Alhusna Izzatulislam; Muhammad Nur; Kumba Digdowiseiso (CV. Syntax Corporation Indonesia, 2024)
The purpose of this study was to determine the effect of taxpayer convenience, taxpayer compliance, and understanding of tax regulations on the use of the M-tax application system services for individual taxpayers at the Pratama Jakarta Matraman Tax Service Office. The population in this study are all individual taxpayers who are actively registered and use the M-tax application at the Tax Office Pratama Jakarta Matraman. The sample selection was carried out using the Slovin formula because in this study the total population was known. Based on certain criteria carried out by the author, the total sample obtained was 99.8 which was then rounded up to 100 samples. The primary data collection method in this study used a questionnaire with direct distribution to individual taxpayers at Tax Office Pratama Jakarta Matraman and several taxpayers filled out the questionnaire link that was distributed. This research uses multiple linear regression analysis technique. Based on the results of the study, it is shown that the convenience of taxpayers and understanding of tax regulations affect the use of the M-tax application. While the taxpayer compliance variable has no effect on the use of the M-tax application.